2013
DOI: 10.1016/j.nut.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restriction interferes with oxidative status and intrinsic intestinal innervation in aging rats

Abstract: The high oxidative status of the aging animals was reversed by dietary restriction, which also lowered cholesterol and triacylglycerol levels. The present dietary restriction elicited morpho-quantitative changes in the myenteric plexus and histology of the ileum, with likely effects on intestinal functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
2
11
0
3
Order By: Relevance
“…It is known that the aging process is associated with a significant number of morphological and functional abnormalities of the gastrointestinal tract, including: the reduced amplitude and frequency of gastric emptying and peristaltic movements, which cause slow intestinal transit (Parker and Chapman, 2004;Schoffen and Natali, 2007); impairment of digestion and nutrient absorption (Schoffen and Natali, 2007) due to lower production of digestive enzymes (Parker and Chapman, 2004;Steegenga et al, 2012); changes in the composition of the intestinal microbiota as a consequence of eating habits (Steegenga et al, 2012;Britton and Mclaughlin, 2013); atrophy of the intestinal mucosa, leading to reduction in its activity (Grattagliano et al, 2004); an increase in the cell cycle (Thrasher and Greulich, 1965;Cirilo et al, 2013); reduction in the apoptotic index of epithelial cells (Holt et al, 1998;Xiao et al, 2001); and (6) neurodegeneration in the enteric nervous system (Drozdowski and Thomson, 2006;Schoffen and Natali, 2007;Cirilo et al, 2013;Mello et al, 2013;Rayner and Horowitz, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the aging process is associated with a significant number of morphological and functional abnormalities of the gastrointestinal tract, including: the reduced amplitude and frequency of gastric emptying and peristaltic movements, which cause slow intestinal transit (Parker and Chapman, 2004;Schoffen and Natali, 2007); impairment of digestion and nutrient absorption (Schoffen and Natali, 2007) due to lower production of digestive enzymes (Parker and Chapman, 2004;Steegenga et al, 2012); changes in the composition of the intestinal microbiota as a consequence of eating habits (Steegenga et al, 2012;Britton and Mclaughlin, 2013); atrophy of the intestinal mucosa, leading to reduction in its activity (Grattagliano et al, 2004); an increase in the cell cycle (Thrasher and Greulich, 1965;Cirilo et al, 2013); reduction in the apoptotic index of epithelial cells (Holt et al, 1998;Xiao et al, 2001); and (6) neurodegeneration in the enteric nervous system (Drozdowski and Thomson, 2006;Schoffen and Natali, 2007;Cirilo et al, 2013;Mello et al, 2013;Rayner and Horowitz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are a range of dietary options being studied for elderly individuals and dietary restriction (DR) is one of the main ones recommended (Holt et al, 1998;Grattagliano et al, 2004;Cencic and Chingwaru, 2010;Reimer et al, 2010;Bauer et al, 2011;Arslan-Ergul et al, 2013;Cirilo et al, 2013;Walsh et al, 2013). Studies performed in the 1930s (McCay et al, 1935) reported for the first time that DR promoted an increase of the maximum life span of experimental animals, such as rats and mice.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that in many neurodegenerative diseases such as the amyotrophic lateral sclerosis and Parkinson's disease, high concentration of NO may lead to cellular death by apoptosis (Singh and Dikshit 2007). Cirilo et al (2013), in studies with 50% dietary restriction and aging, analyzed myenteric population HuC/D, subpopulation nNOS and glial cells in rats 7-12 months old, and found that aging did not cause changes in any of the populations studied, however, with dietary restriction, a significant decrease of the population HuC/D and glial cells, without affecting the population nitrergic. In addition, with aging beyond death of neurons, is reported quantitative decrease in the population of enteric glia, which plays an important role in maintaining the enteric nervous system (Phillips et al 2004).…”
Section: Discussionmentioning
confidence: 98%
“…Changes in the cellular profile area of the myenteric neurons are reported under experimental conditions involving diabetes mellitus (Furlan et al 2002), under nutrition (Castelucci et al 2002 and dietary restriction (Cirilo et al 2013). According to authors the increase of neurons size is usually confirmed during animal development (Gabella 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation